Genetic diversity and heritability of seed characters of soybean genotypes (Glycine max (L.) Merril) F3 generation in rainy season planting - Acep Atma Wijaya; Karmila Mila (Fakultas Pertanian Universitas Yudharta Pasuruan, 2026)
Introduction: Soybeans an important source of vegetable protein. Soybean production in Indonesia is still low and needs to be increased. One strategy is to increase the frequency of planting during the rainy season. Soybean development during the rainy season requires information on genetic diversity and heritability. The purpose of this study was to analyze the genetic diversity and heritability of F3 generation soybean lines planted during the rainy season. Methods: The experiment was used randomized block design (RBD).Tthe Least Significant Increase (LSI) test at the 5% level is used to see the difference in appearance of the test line with the check variety. Genetic parameters was analyzed by estimating genetic and phenotypic variance, and heritability. Results: The results showed that genotype UM002 differed significantly from the check cultivar in seed number per plant, and 100-seed weight showed wide genetic variability with high heritability. Seed length, width, and thickness also showed wide genetic variability with moderate heritability. In contrast, seed yield per plant showed low heritability and narrow genetic variability, suggesting a more substantial environmental influence. Conclusion: UM002 line showed better seed number performance per plant compared to two check varieties, Deja 2 and Detam 4, which can be used as a promising soybean line that is adaptive to the rainy season. The 100-grain weight character showed a high heritability value. This indicates that the 100-grain weight character can be used as a selection criterion for soybeans during the rainy season in an effort to increase selection effectiveness.